Heavenly journeys, earthly concerns : the legacy of the miʻraj in the formation of Islam - Vuckovic, Brooke Olson (New York : Routledge, 2005)
Examines how an elite group of traditionists, historians and theologians shaped Muslims' perceptions of their prophet, their community and their behaviour by retelling and interpreting the story of Muhammad's ascent to heaven (the mi'raj).
Constructing the prophet of God -- The miʻraj and the early Muslims' communal and confessional identity -- Communal reaction -- The formation of communal morality.
Includes bibliographical references (pages 137-176) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Muḥammad, -- Prophet, -- -632 -- Isrāʼ and Miʻrāj.; Muḥammad, -- Prophet, -- -632 -- Anecdotes; Mahomet, -- le prophète, -- -632 -- Isrā' et Miʻrāj.; Muḥammad, -- Prophet, -- -632; Muḥammad, -- ca.570-632.; Islam -- Origin; Ummah (Islam); Electronic books; Islam -- Origines; Ummah (Islam); Livres numériques.; e-books.; 11.82 Islamic traditional literature; RELIGION -- Islam -- General; Islam -- Origin; Ummah (Islam); Anecdotes